A Matryoshka-like seismic metamaterial with wide band-gap characteristics. (1st March 2020) - Zeng, Yi; Xu, Yang; Yang, Hongwu; Muzamil, Muhammad; Xu, Rui; Deng, Keke; Peng, Pai; Du, Qiujiao
Abstract: Seismic surface waves, composed of many complex waves and difficult to attenuate, can be controlled and obstructed by seismic metamaterials applied in civil engineering to protect sensitive buildings, such as nuclear power plants and ancient buildings. In this paper, a seismic metamaterial based on Matryoshka-like structure is designed. The dispersion curves and transmission are simulated by using finite element method. Comparative study on the dispersion curves of Matryoshka-like seismic metamaterial with different layers shows that the more layers the Matryoshka has, the more band gaps, the more resonant modes and the wider band gap are provided. Moreover, the vibration modes for Matryoshka-like seismic metamaterial are computed and analyzed to clarify the mechanism of widening band gaps. And the effectiveness of the Matryoshka-like seismic metamaterial in attenuating surface waves within the 0.1–13.1 Hz regime are demonstrated. Although we focus on geophysical structure, the proposed metamaterial provides possible alternative for various phenomena such as the vibration and noise attenuation because the center frequencies of band gaps can be easily achieved by modulating the material and geometrical parameters.